POTENTIAL BRAIN-DEAD ORGAN DONORS: CHARACTERIZATION AND IDENTIFICATION OF NURSING DIAGNOSES - Bezerra, Gabriela Duarte; Clementino, Kyohana Matos de Freitas; Silva, Maria Isabel Caetano da; Domingos, João Emannuel Pereira; Araújo, Isaac de Sousa; Vidal, Eglídia Carla Figueirêdo; Pinheiro, Woneska Rodrigues (Cogitare Enfermagem, 2023)
Objective: To identify the nursing diagnoses of potential organ donors in brain death according to the NANDA-I Taxonomy. Method: Observational, cross-sectional study conducted in a public hospital in the interior of Ceará, Brazil. Data collection was realized in October and November 2021 in 23 medical records of potential organ donors. Descriptive statistics analyzed data. Results: Twenty-two diagnoses were identified in five of the 13 domains of the NANDA-I taxonomy. The following were prevalent: risk of unstable blood glucose; risk of impaired liver function; impaired gas exchange; impaired bed mobility; ineffective breathing pattern; risk of infection; risk of pressure injury; risk of aspiration; risk of decreased cardiac output; risk of falls, impaired urinary elimination; risk of electrolyte imbalance and risk of unstable blood pressure. Conclusion: The identification of diagnoses may favor the improvement of practice and the application of the nursing process in the care of potential organ donors.